Relationship between Prosopis juliflora invasion and livelihood diversification in the South Afar region, Northeast Ethiopia - Shiferaw, W.; Demissew, S.; Bekele, T.; Aynekulu, E. (Elsevier, 2020)
This study assessed the effects of Prosopis juliflora invasion on livelihood diversification and evaluated the determinants of livelihood diversification in two districts in the South Afar region of Northeast Ethiopia. Using random sampling method, 154 households and 2 focus groups composed of 10 individuals were selected from four sites in the two districts. The relationship between P. juliflora invasion and incomes obtained from P. juliflora varied across the study sites. In Awash Fentale District and Amibara District, 11.0% and 3.2% of households, respectively, earned income from P. juliflora charcoal production. In total, 14.3% of households were involved in charcoal production. In addition, 19.9% of households earned income from selling P. juliflora pods and wood materials in the two districts. With the exception of income from P. juliflora charcoal production, the sex of households did not affect incomes from other livelihood activities. Moreover, household educational attainment significantly affected income obtained from vegetables, fruits, and cereal crops. Male householders were engaged in more diverse livelihood activities than female householders. Reversing the severe invasion of P. juliflora on grazing and woodlands in the region is advisable through integrated natural resources, pastoralist participation, and multidisciplinary research strategies.